English orientating constructions denoting location: classification and article use - Talavira, Nataliia (Lingua Posnaniensis, 2017)
The paper singles out English orientating constructions which refer to constant coordinates meant to position situational changeable entities, e.g. at eye level, on hand, in part, in detail. The analysis of constructions denoting location reveals their entrenchment in mind in the basic – articleless – form representing situation coordinates on the superordinate categorization level. Orientating constructions have two discursive variants depending upon the article in their structure: definite and indefinite. The definite article refers to the reference points imposed by a particular situation which is signalled by the combination of orientating and extending constructions while the indefinite article points to the establishment of new coordinates.